Workshop Report - Corridors, Clusters and Spatial Development Initiatives - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2016)
An ISPC workshop on “Corridors, Clusters, and Spatial Development Initiatives in African Agriculture” was held on 30 November 2015 as a side event of the Global Forum for Innovations in Agriculture in Africa in close collaboration with NEPAD-CAADP and the European Centre for Development Policy Management. The workshop report also contains the list of participants.